Cavernous Hemangioma of the Orbit and Its Impact on Orbital Fat - O. Yu. Yatsenko (Oftalʹmologiâ)
The most common representative of primary tumors is a cavernous hemangioma of the orbit, which can lead to the disorder of functions of an eye and a cosmetic defect. The literature has repeatedly described the clinical picture of patients with cavernous hemangioma, their CT semiotics, hemangiomasintercourse with orbital structures. However, there is no data about the effect of the tumor on the state of the orbital fat.The purpose — to study structural features of cavernous hemangiomaand toundertake a study of state of the orbital fat, depending on the size of tumors.Patients and methods. We studied 36 patients with cavernous hemangioma of the orbit. CT scans were performed according to standard procedures to give axial and frontal slices. Volumetric soft tissues of the orbit indicators obtained after the construction of three-dimensional models. Originally built a three-dimensional reconstruction of the osseous orbit outside the orbit's part of the eye, and then — a muscular channel and soft tissue reconstruction unit (extraocular muscles, the optic nerve, lacrimal gland and eyes). We calculate the orbit of the eye and orbital fat. The volume of the orbital part of the eye obtained by subtracting the volume of the volume of its eyes outside the orbit’s part. The amount of fiber internal surgical space obtained by subtracting from the muscular channel volume of extraocular muscles and optic nerve. Control in all cases was a healthy contralateral orbit.Results and discussion. It was found that an increase in the volume of tumors occurssubatrophy of orbital fat. In patients with smallhemangiomas the amount of orbital fat is reduced by about 0.5 cm3, in patients with an average hemangiomasthe amount of orbital fat is retracted more than 1 cm3. The most prominent orbital fat atrophy in theorbitlocalization of large cavernous hemangiomas (on 2,88±0.09 cm3).Conclusions. An increase in the size of cavernous hemangioma leading to its structural changes, and the development of orbital fatsubatrophy.